Sarjan Hassan - Avellano, Lamberto V. ([S.l.] : Malay Film Production [production company] ; Kuala Lumpur : Sathya Production [distributor])
Mengisahkan seorang perajurit yang sanggup bekorban demi agama, bangsa dan negara.
Editor, Ahmad Johari, H. R. Narayana ; story, Ralph Modder
P. Ramlee (Hassan), Saadiah (Salmah)
Keywords: Armed Forces in motion pictures; Nationalism in motion pictures -- Malaysia